2016
DOI: 10.1038/srep34375
|View full text |Cite
|
Sign up to set email alerts
|

Sorting cells by their dynamical properties

Abstract: Recent advances in cell sorting aim at the development of novel methods that are sensitive to various mechanical properties of cells. Microfluidic technologies have a great potential for cell sorting; however, the design of many micro-devices is based on theories developed for rigid spherical particles with size as a separation parameter. Clearly, most bioparticles are non-spherical and deformable and therefore exhibit a much more intricate behavior in fluid flow than rigid spheres. Here, we demonstrate the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 33 publications
3
78
0
1
Order By: Relevance
“…Traditional methods, such as ektacytometry 28,29,54,55 , test the rheological properties of RBC derived from bulk flow, which does not correlate well with circulatory clearance time 56,57 . Microfluidic technologies present the potential to improve upon this measurement process by using microfabricated structures to approximate the deformation mechanics of the splenic microvasculature [58][59][60] . However, key limitations of existing microfluidic devices is the throughput of the measurement process, as well as sample-to-sample consistency.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional methods, such as ektacytometry 28,29,54,55 , test the rheological properties of RBC derived from bulk flow, which does not correlate well with circulatory clearance time 56,57 . Microfluidic technologies present the potential to improve upon this measurement process by using microfabricated structures to approximate the deformation mechanics of the splenic microvasculature [58][59][60] . However, key limitations of existing microfluidic devices is the throughput of the measurement process, as well as sample-to-sample consistency.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the molecular beam studies indicated that the larger Pd NPs greatly decrease the adsorption energy from the asymptotic value of Pd(111). [65,66] On the other hand, the adsorption of HCOO À is favoured in the smaller Pd NPs, which unfortunately leads to space exclusion and repulsive adsorbate-adsorbate interaction and finally declines the catalytic performance in the H 2 production. [42] Therefore, it seems that achievement of a properly balanced surface state possessing the higher reactivity of the smaller metal NPs and the higher coverage of intermediate species is mandatory to obtain optimal catalysts in the formic acid dehydrogenation.…”
Section: Mechanistic Investigationmentioning
confidence: 99%
“…2). Developments include microfluidic systems for cell culture (Halldorsson, Lucumi, Gómez-Sjöberg, & Fleming, 2015; Moreno et al, 2015; Rhee et al, 2005; Young & Beebe, 2010), sorting (Henry et al, 2016; Krüger et al, 2002; Siedlik, Varner, & Nelson, 2016; Ung et al, 2017; Warkiani, Wu, Tay, & Han, 2015), manipulation (Applegate, Squier, Vestad, Oakey, & Marr, 2004; Chen, Chen, Chen, Jang, & Wang, 2014; Ding et al, 2012; Yi, Li, Ji, & Yang, 2006; Yun, Kim, & Lee, 2013; Zhao, Cheng, Miller, & Mao, 2016), and bioanalysis (Chen, Li, et al, 2014; Mirasoli, Guardigli, Michelini, & Roda, 2014; Wheeler et al, 2003). The research field of microfluidics continues to expand as novel strategies for stimulation and analysis continuously emerge.…”
Section: Design Considerations For Microfluidicsmentioning
confidence: 99%